Genetic improvement of the BR 5033-Asa Branca corn cultivar in the Brazilian Northeast region - Carvalho, Hélio Wilson Lemos de; Santos, Manoel Xavier dos; Leal, Maria de Lourdes da Silva; Carvalho, Paulo Cesar Lemos de (Pesquisa Agropecuaria Brasileira, 2000)
Five cycles of selection were carried out among and within progenies of half-sibs on the BR 5033-Asa Branca corn cultivar, within the 1993 to 1997 period, in the Northeast Brazil, in order to obtain a germplasm more productive and better adapted to the ecological conditions of the region. The progenies were evaluated in a lattice 14 x 14, with two replications, using the recombination in the same agricultural year, aiming to obtain a generation per year. The genetic variability of the cultivar decreased as the cycles of selection advanced; this reduction was more pronounced in the cycles III and IV, when the selection was done in two and three places, respectively, and was less influenced by the interaction of progenies x places. The high magnitudes of the genetic parameters have shown that the cultivar BR 5033 has a high genetic variability, that gives perspective of subsequent gains in the production by selection, that associated to a good yield and to its precocity, makes this cultivar to be an important alternative for the agriculture in the Northeast.